MINERAL METABOLISM FEATURES IN TURKEYS - Rebezov, Yaroslav; Gorelik, Olga; Bezhinar, Tatyana; Safronov, Sergei; Vinogradova, Natalia; Ermolova, Yevgenia; Shcherbakov, Pavel; Gritsenko, Svetlana; Stepanova, Ksenia (International Journal of Psychosocial Rehabilitation, 2020)
Mineral substances are essential for the synthesis of vital compounds and are part of the molecules of complex organic structures. The aim of the research is to study mineral metabolism features of turkeys of different genotypes and age. It was established that the condition of calcium-phosphorus metabolism determined by the level of total calcium and inorganic phosphate in blood depends on the age and cross of birds. The content of macroelements of Heavy Cross Hybrid Converter turkeys exceeds its analogues by 3.21-14.72%. At the same time, the concentration of calcium during the growth of turkey organism increases, and phosphate - decreases, determining the increase of Ca : P - ratio in 60-day age from 1.44 - 1.49 conventional units to 1.74 - to 1.85 conventional units in 120-day age. The level of reserve alkalinity of blood is correlated with the age and genotype of birds. Its value decreases during the growth of the organism, reflecting the metabolic processes in cells of organs and tissues, during which a large number of acidic metabolites are formed. The volume of alkaline stocks decreases most strongly in the blood of Heavy Cross Hybrid Converter turkeys (group IV), indicating a higher level of metabolism in their bodies.